Rene Policistico e trapianto di rene: accesso alla lista d'attesa e post trapianto: risultati della ricerca - Rossana Caldara (AboutScience Srl, 2019)
Autosomal-dominant polycystic kidney disease (ADPKD) is the leading genetic cause of end-stage renal disease (ESRD) worldwide. The number of ADPKD patients who are listed for transplantation or receive a kidney transplant is continuously increasing over time. AIRP conducted a survey to investigate the ADPKD patient journey, meaning the personal experience and expectations of people regarding kidney transplantation as therapeutic option of end-stage renal failure. The survey was conducted on 381 people with ADPKD, using computer-assisted web interviewing (CAWI). The results confirm that there are problems that need to be addressed before listing an ADPKD patient for a kidney transplantation, namely the patient's comorbidities, the complexity of pre-transplant assessments and the shortage of organs. Pre-emptive transplantation from cadaver donor is a rare event in our country but it is a valid option, especially in case of living donation. Immunosuppression is well tolerated in a high percentage of subjects, but a follow-up is necessary to monitor negative side effects. Despite these problems, the outcome of kidney transplantation is optimal in these patients. Also, the relationship between patients and Nephrologists and/or Transplant Centers is important to ensure a positive outcome.